ANALISIS ATRIBUT PRODUK YANG DIPERTIMBANGKAN KONSUMEN DALAM PEMBELIAN HANDPHONE BLACKBERRY - Wahyu Eko Pujianto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
The study is done at the University of Muhammadiyah Sidoarjo. While samples from this research is stdudent use cellular phones blackberry in Sidoarjo Muhammadiyah University in March 2012, 120 students . To use the method of analysis of data analysts factors. The result showed that the factors be considered at the purchase of products handpone blackberry is the blackberry facilities and email , facilities and facilities fourshared browsing /google, facilities of facebook, service, on the menu blackberry and the brand image, the facility yahoo messenger, and memory capacity, reliable. Cellular phone prices blackberry. First factor viii has important up to produce outputs in the consumers in buying the cell phone blackberry shown by the value of cumulative total varians mncapai 72,308 %, by a factor of I as much as 14,112 %, factors II of 11,376 %, third factor of 10,821 %, fourth factor of 9,776 %, factor IV of 9,776%, factor V of 7,399%, factor VI of 6,936%, factor VII of 6,209%, factor VIII of 5,678%.